Agar/β-Cyclodextrin Composite Cryogels for Controlled Release of Aripiprazole - Siyka Stoilova; Georgy L. Georgiev; Rositsa Mihaylova; Bistra Kostova; Petar D. Petrov (Molecules)
Aripiprazole (ARZ) is an atypical antipsychotic drug used to treat a variety of mood and psychotic disorders, such as schizophrenia, bipolar disorder, major depressive disorder, autism, and Tourette’s syndrome. Although ARZ offers significant therapeutic benefits, its poor solubility in water requires the development of delivery systems aimed at improving the solubility and bioavailability of the drug. In this work, cryogels based on two natural products—agar and β-cyclodextrin (CD)—were developed and evaluated as a drug delivery system for ARZ. The cryogels were prepared by cryogenic treatment of aqueous solutions of agar and the β-CD/ARZ complex, followed by thawing. The main characteristics of the material, including gel fraction yield, swelling degree, pore volume, elastic properties, and morphology were studied in detail. The release of ARZ from composite cryogels was assessed in two media resembling the pH in stomach and intestine. The system exhibited a pH-dependent release of ARZ, with a slower rate in acidic media (pH 1.2) than in the neutral phosphate buffer (pH 6.8). Under in vitro conditions, the amount of released ARZ over 48 h reached 33%.